Optimization of the Breeding Conditions of Aspergillus niger for En-zyme Production Focusing on Temperature, Substrate Source, Nitro-gen Source, Carbon Source, and pH - Matongorere, Marcia; Madingi, Tanaka; Mangoyi, Rumbidzai (BioScientific Review, 2026)
Background. Aspergillus niger is extensively employed in the industry to produce organic acids, enzymes, and other metabolites. Optimizing the breeding conditions for A. niger to increase enzyme yields and boost the effectiveness of industrial fermentation processes is a crucial field of study. Methods The effects of different temperature conditions (15°C, 30°C, and 45°C), carbon sources (oats, wheat, corn, and sugar cane), nitrogen sources (NH4NO3, NH4CL, and (NH4)2SO4), and pH (4, 7, and 10) on the production of enzyme amylase were determined. A. niger was fermented under controlled conditions in bioreactor shake flasks and enzyme activities were measured using standard colorimetric and fluorometric assays. Results. The results showed an optimum temperature of 30°C for A. niger fermentation for the production of amylase, with the highest specific enzyme activity of 1.1 U/mg. NH4SO4 was found to be the best nitrogen source for the fermentation of A. niger for enzyme production. Whereas, wheat and corn proved to be the best carbon sources for the fermentation of A. niger for enzyme production. Wheat and corn produced amylase with the specific enzyme activity of 0.63 U/mg. The pH 4 was found to be ideal for the fermentation of A. niger for enzyme production The enzyme produced at pH 4 showed a specific enzyme activity of 0.5 U/mg. Conclusion. The results suggest a positive correlation between optimising the breeding conditions of A. niger and the quality of amylase produced. It provides valuable insights to guide the scale-up and commercialization of A. niger-based bioprocesses for industrial enzyme manufacturing.